Microstructural and mechanical properties of nano-yttria-oxide doped hydroxyapatite composites - (:unkn) unknown (Trans Tech Publications Ltd, 2018)
Nowadays hydroxyapatite (HA) bioceramics are very important because increasing traffic accidents and ageing of the population. They can be produced from synthetic or natural sources with different production methods. The biggest negative issue of HA is being very brittle and unstable under pressure. Various materials are added for restoring these weaknesses, but there is not so much studies adding nano-ingredients for restoring the mechanical properties of HA. In this study, 5-10% nano-yittria-oxide is added to bovine derived HA (BHA) and to commercial synthetic (CSHA) as a control group. Physical and mechanical properties are examined. Results show that adding of nano-ingredients are really helping to mechanical properties of HA. © 2018 Trans Tech Publications, Switzerland.
Keywords: Composites; Hydroxyapatite; Mechanical properties; Nano-dopants; Yttria